Ginsenoside Rb1 attenuates coronary microvascular inflammatory injury via NDUFS4-SIRT5-DUSP1-mediated mitochondrial quality control in a murine ischemia-reperfusion model - Xiangyi Pu; Jinfeng Liu; Yanli Wang; Xuanke Guan; Qiaomin Wu; Qin Zhang; Ruxiu Liu; Xing Chang (Journal of Ginseng Research)
Background: Ginsenoside Rb1 is a prominent bioactive component in traditional Chinese medicine. Purpose: This study investigated the molecular mechanisms underlying the protective effects of Ginsenoside Rb1 on endothelium during ischemia-reperfusion (I/R) injury. Materials and methods: To enrich for marker genes and investigate the differential expression of DUSP1 and NDUFS4 in coronary artery disease, single-cell transcriptome sequencing was utilized. SIRT5CKO/TG and NDUFS4CKO/TG mouse models were established using gene modification techniques. Si-DUSP-1/ad-DUSP-1 and si-SIRT5/ad-SIRT5 cell models were constructed. Fluorescence detection, mitochondrial membrane potential assays, RT-PCR, and Western blotting were employed to detect the mitochondrial function. Results: NDUFS4 and DUSP1 regulate the mitochondrial unfolded protein response (mtUPR), energy metabolism, and dynamics, and may be crucial regulatory genes in the development of coronary artery disease. Ginsenoside Rb1 modulates the NDUFS4-SIRT5-DUSP1 axis, regulates the mitochondrial quality control network, and alleviates coronary microvascular inflammatory injury. Conclusions: Ginsenoside Rb1 regulates the NDUFS4-SIRT5-DUSP1 axis, modulating the mitochondrial quality control network, inhibiting the inflammatory cascade response, and improved myocardial function.